Acute effects of virtual reality exercise bike games on psychophysiological outcomes in college North-African adolescents with cerebral palsy: A randomized clinical trial [version 3; peer review: 1 approved, 2 approved with reservations] - Mehdi Chlif; Amine Ghram; Makrem Soudani; Faical Farhat; Helmi Ben Saad (F1000Research)
Background Cerebral palsy (CP) is a neurological disorder that can affect motor skills and psychophysiological well-being. Virtual Reality Exercise (VRE) improves cognitive and physical outcomes in patients with CP. Therefore, this study aimed to investigate the effects of VRE on attention, vigor, and decision-making abilities in adolescents with CP. Methods A randomized controlled trial was conducted. The intervention consisted of a single 40-minute session of VRE compared to TE conducted in a controlled laboratory environment. Results Fourteen participants (42.9 % female) were included in this analysis. The results indicated that VRE had a statistically significant positive effect on attention and vigor compared to TE. While participants in the VRE group exhibited enhanced attention levels and reported elevated levels of vigor subsequent to the exercise sessions, the memory results did not reach statistical significance. Conclusions The findings suggest that VRE is an effective intervention for improving attention and vigor in adolescents with CP. Registration Pan African Clinical Trial Registry (PACTR202308598603482; 31/08/2023). The trial was reported in accordance with the CONSORT reporting guidelines.